Southpaw - Wallace, Rich. (New York : Viking, 2006)
After moving to New Jersey following his parents' divorce, Jimmy Fleming tries out for the seventh-grade baseball team while also trying cope with his new life and dealing with his overly-competitive father.
Accelerated Reader AR
Keywords: Baseball -- Fiction; Fathers and sons -- Fiction; Divorce -- Fiction; Moving, Household -- Fiction; Schools -- Fiction